Epigenetic regulation of cardiac myocyte differentiation† - Oyama, Kyohei; El-Nachef, Danny; Zhang, Yiqiang; Sdek, Patima; MacLellan, W. Robb (Frontiers in Genetics, 2014)
Cardiac myocytes proliferate robustly during fetal life but withdraw permanently from the cell cycle soon after birth and undergo terminal differentiation. This cell cycle exit is associated with upregulation of a host of adult cardiac-specific genes. The vast majority of adult cardiac myocytes do not reenter cell cycle even if subjected to mitogenic stimuli. The basis for this irreversible cell cycle exit is related to stable silencing of cell cycle genes specifically involved in the progression of G2/M transition and cytokinesis. Studies have begun to clarify the molecular basis for this stable gene repression and have identified epigenetic and chromatin structural changes in this process. In this review, we summarize the current understanding of epigenetic regulation of cardiac myocyte cell cycle and cardiac specific gene expression with a focus on histone modifications and the role of retinoblastoma family members.